Have you heard the news? How real-life expectations react to publicity - Karen van der Wiel (Institute for the Study of Labor (IZA), 2009)
As evidence is accumulating that subjective expectations influence behavior and that these expectations are sometimes biased, it becomes policy-relevant to know how to influence individuals' expectations. Information in the media is likely to affect how people picture the future. This paper studies the role of public information dissemination, or publicity, in a real-life expectations formation process. For this purpose, an exceptional Dutch dataset on monthly expectations regarding the future eligibility age for old age social security is analyzed. On average, the publicity reaction in eligibility age expectations is small but the differences among subgroups are considerable. I find that higher educated and high income groups hardly adapt their expectations to relevant publicity. On the contrary, those who do not often read a newspaper have a relatively high publicity reaction. A potential explanation for this latter finding is that these groups have low quality initial expectations. If this is true, publicity thus particularly benefits the initially worse informed groups.
urn:nbn:de:101:1-20090327323
Keywords: D83; D84; H55; 330; Expectations; information; media; Erwartungstheorie; Anpassung; Informationsverhalten; Zeitung; Öffentliche Meinung; Altersgrenze; Gesetzliche Rentenversicherung; Theorie; Niederlande